Mobility-Non-Exercise Physical Activity (NEPA) is the key to health and longevity - Margaret Arnold; Joan Vernikos (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
When asking someone, whatever their age, what they consider most important to their health, the answer invariably involves their ability to maintain physical independence-basic mobility. The highest level of mobility is unlimited movement in any environment they choose. As mobility is lost, the environments in which independent movement is possible, become restricted. As mobility is further compromised, an assistive device may be needed such as a walker or a cane, then with further decline, the person may begin to rely on help for more and more movements, and their independence is replaced by dependence on another for help. The impact of declining mobility on health and well-being, both physical and psychological are substantial and reduced mobility and ability to do Instrumental Activities of Daily Living (IADL) can often be the first sign of declining health Table 1.